Загальна хмарність в Україні до середини ХХІ ст. за даними ансамблю регіональних кліматичних моделей - Краковська, С.В.; Паламарчук, Л.В.; Білозерова, А.К.; Шпиталь, Т.М. (Геоінформатика, 2017)
Проведено аналіз особливостей просторово-часового розподілу загальної хмарності в Україні за даними Кліматичного кадастру України для періоду 1961—1990 рр., за даними спостережень метеорологічної мережі для періоду 1981—2000 рр. і до середини ХХІ ст. за даними верифікованого ансамблю регіональних кліматичних моделей. Наведено методичні підходи до вибору оптимального ансамблю моделей для створення прогностичних полів загальної хмарності у майбутні кліматичні періоди на підставі даних спостережень і статистичного аналізу. Проведен анализ пространственно-временных особенностей распределения общей облачности в Украине по данным Климатического кадастра Украины для периода 1961-1990 гг., по данным наблюдений метеорологической сети для периода 1981-2000 гг. и до середины XXI ст. по данным верифицированного ансамбля региональных климатических моделей. Представлены методические подходы к выбору оптимального ансамбля моделей для создания прогностических полей общей облачности в будущих климатических периодах на основе данных наблюдений и статистического анализа. Purpose. The paper analyzes the features of spatiotemporal distributions of total cloud cover (TCC) in Ukraine for the past and future climatic periods. TCC and the number of clear and overcast days were analyzed based on the data from the Klimatychnyi Kadastr Ukrainy (Inventory of Climate in Ukraine) for the Standard WMO climatic period 1961-1990. The observation data at 9 meteorological stations evenly covering the territory of Ukraine in the period of 1961-2000 serve as a benchmark for verification and bias correction of regional climate models (RCMs) from the FP-6 ENSEMBLES initiated with boundary conditions from ERA-40 for 1961-2000 and IPCC SRES A1B for 1951-2050 (ensembles-eu.metoffice.com). Design/methodology/approach. Verification of 12 RCMs by statistical analysis has shown the following: while the data of any individual RCM can have significant absolute errors affecting the reliability of projected characteristics, systematic errors of ensembles of RCMs are in general less significant and can be corrected based on the observational data in the past periods. The paper presents an original methodology of RCM verification and bias correction, which permits to identify and form for TCC an optimum ensemble of 9 RCMs initiated with different Atmosphere-Oceans Global Circulation Models that ensure maximum completeness and range of TCC under possible future climatic scenarios.
Findings. Spatiotemporal distributions of TCC in Ukraine for the periods of 2011-2030 and 2031-2050 calculated with the verified and bias-corrected ensemble of 9RCMs showed an overall decrease of annual TCC by 1-2% in both periods, with maximum values in spring and summer seasons up to 3%, while for winter seasons slight increase of TCC by 1% is projected. The obtained maps of expected annual and seasonal TCC changes show spatial inhomogeneity and allow us to analyze regional features in both future periods.
Practical value/implications. The obtained spatiotemporal distributions of TCC can serve as a basis for further research and evaluation of recent and future changes in other climate indicators associated with TCC and for many scientific fields and economic sectors related to and dependant on climate characteristics till the middle of the 21st century: agrometeorology, hydrology, biology, ecology, agriculture, energy, construction, transport, tourism, health care, recreation and others.